Carbon Nanosphere-Based TiO2 Double Inverse Opals - Dániel Attila Karajz; Kincső Virág Rottenbacher; Klára Hernádi; Imre Miklós Szilágyi (Molecules)
Inverse opals (IOs) are intensively researched in the field of photocatalysis, since their optical properties can be fine-tuned by the initial nanosphere size and material. Another possible route for photonic crystal programming is to stack IOs with different pore sizes. Accordingly, single and double IOs were synthesized using vertical deposition and atomic layer deposition. In the case of the double IOs, the alternating use of the two preparation methods was successfully performed. Hydrothermally synthesized 326 and 458 nm carbon nanospheres were utilized to manufacture two different IOs; hence the name 326 nm and 458 nm IOs. Heat treatment removed the sacrificial template carbon nanospheres, and the as-deposited TiO2 crystallized upon annealing into nanocrystalline anatase form. Reflectance mode UV–visible spectroscopy showed that most IOs had photonic properties, i.e., a photonic band gap, and by the “slow” photon effect enhanced absorbance, except the 326 nm IO, even though it also had an increase in absorbance. The IOs were tested by photocatalytic degradation of Rhodamine 6-G under visible light. Photocatalytic experiments showed that the 458 nm IO was more active and the double IOs showed higher efficiency compared to monolayers, even if the less effective 326 nm IO was the top layer.